Pharmacokinetics and liver uptake of three Schisandra lignans in rats after oral administration of liposome encapsulating β-cyclodextrin inclusion compound of Schisandra extract. (3rd April 2019) - Ding, Zhiying; Xiao, Jiajing; Zhang, Yue; Jiang, Yueyao; Chen, Weiqiang; Hu, Jiahui; Guo, Yu; Zhang, Bingren
Abstract: Schisandra chinensis fructus (SCF) is widely used traditional Chinese medicine, which possesses hepato-protective potential. Schisandrin (SD), schisantherin (ST), and γ-schizandrin (SZ) are the major bioactive lignans. The main problem associated with the major bioactive lignans oral administration is low oral bioavailability due to the lignans' poor aqueous solubility and taste. The aim of the present research work was to develop liposome (SCL) encapsulated β-cyclodextrin (β-CD) inclusion complex loaded with SCF extract (SCF-E). The SD, ST, and SZ were selected as effective candidates to perform comparisons of liver targeting among the solution (SES), β-cyclodextrin inclusion compound (SCF-E-β-CD), liposome (SEL), and SCL of SCF-E to characterize the pharmacokinetic behaviors and liver targeting in rats. The β-CD inclusion complex (SCF-E-β-CD) was used to improve the solubility. The concentrations were determined using high-performance liquid chromatography (HPLC) and analyzed by DAS3.0. The pharmacokinetic results indicate that the plasma concentration-time courses were fitted well to the one-compartment model with the first weighing factor. The half-life period ( t 1/2 ) and area under the concentration-time curve (AUC) of the three components in SCL were the largest. The SCL exhibit a relatively high liver targeting effect. The results would be helpful for guiding the clinical application of this herbal medicine.